2014
DOI: 10.1111/ppa.12275
|View full text |Cite
|
Sign up to set email alerts
|

High genotype diversity and lack of isolation by distance in theAlternaria solanipopulations fromChina

Abstract: A genomic library was used to develop seven SSR markers for studying the population genetics of Alternaria solani, a pathogenic fungus causing early blight disease of potato and tomato worldwide. Population genetic analysis of 268 isolates of A. solani sampled from four locations, each representing one of four potato production systems in China, indicates that these SSR markers are moderately diverse, selectively neutral and possibly unlinked. Population genetic analysis also indicated that genetic variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…Using ISSR, Meng et al [31] found a diversity of genotypes of A. solani in four regions in China. The authors found that 268 isolates demonstrated high genetic variation within populations of the same location and found no genetic differences between collection sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ISSR, Meng et al [31] found a diversity of genotypes of A. solani in four regions in China. The authors found that 268 isolates demonstrated high genetic variation within populations of the same location and found no genetic differences between collection sites.…”
Section: Discussionmentioning
confidence: 99%
“…According to Meng et al [31] each species of fungus has an ideal temperature range for sporulation, which is reduced at low temperatures and increases with the increase in temperature until reaching a point of maximum sporulation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in USA, Cuba, Brazil, India and China using isozyme and molecular markers also found no location effect or no clear differentiation of A. solani collected from various regions in those countries (Petrunak and Christ 1992;Weir et al 1998;Martinez et al 2004;Varma et al 2006;Kumar et al 2008;Lourenço et al 2011;Leiminger et al 2013;Meng et al 2015). Isolates from different agroclimatic conditions were found to be more genetically similar than isolates in close proximity to one another (Kumar et al 2008).…”
Section: Aflp Polymorphism and Phylogenetic Analysismentioning
confidence: 99%
“…Previous studies revealed considerable variability among isolates with respect to morphology, physiology, biochemistry, aggressiveness and genetics (Bonde 1929;Henning and Alexander 1959;Petrunak and Christ 1992;Weir et al 1998;Castro et al 2000;Martinez et al 2004;van der Waals et al 2004;Varma et al 2006;Lourenço et al 2009;Lourenço Jr et al 2011;Weber and Halterman 2012;Meng et al 2015;Kumar et al 2016;Odilbekov et al 2016). Great variability in A. solani is unexpected, since the sexual stage of this pathogen is not known (Meng et al 2015). The occurrence of differential aggressiveness among isolates has led to the conclusion for the presence of physiological races (Bonde 1929).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation